Granulomatous lipophagic panniculitis and temporal arteritis in a patient with cryptogenic chronic active hepatitis. Issue 6 (June 1992) - Naschitz, J E; Yeshurun, D; Barth, J; Misselevitch, I; Boss, J H
Abstract : An elderly woman receiving long term treatment with prednisone and azathioprine for cryptogenic chronic active hepatitis developed granulomatous lipophagic panniculitis and temporal arteritis. The lymphoplasmahistiocytic inflammatory reaction pattern is common to this patient's three diseases. It is suggested that an aberration of the defence mechanisms, immunological or otherwise, is responsible for this unusual occurrence. The triple association of chronic active hepatitis, granulomatous panniculitis and temporal arteritis has not been reported previously.